KAJIAN PENERAPAN MANAJEMEN RISIKO K3 PADA PROYEK PEMBANGUNAN RUMAH SAKIT KECAMATAN PONTIANAK UTARA - Cindy Andara Yosefine; Safaruddin M Nuh; Riyanny Pratiwi (JeLAST : Jurnal Teknik Kelautan , PWK , Sipil, dan Tambang, 2022)
Occupational safety and health is the goal of every construction activity to improve the welfare of the workers in a construction project in order to create good construction results. Currently, work accidents have become a concern in every service industry, especially the construction industry, so accidents are said to have causes and solutions to prevent them. During the pandemic, construction implementation decreased greatly, so during the recovery period, construction implementation increased. Attention to Occupational Safety and Health or K3 has become a serious matter because it has an influence on several aspects. K3 risk management is a mandatory thing to be applied in the implementation of construction work. Completeness of K3 documents is also a requirement for the implementation of construction projects. Assessment of high-risk levels will be followed up by the analysis using the JSA (Job Safety Analysis) method. Prevention of risk from hazard identification can be minimized by planning controls that are adjusted to the SOP for K3 construction. The successful implementation of a construction project is to be able to produce zero accidents in the construction project. The construction project of the North Pontianak District Hospital became the object of research in this study of the K3 risk management system in accordance with existing regulations.